Incidence, risk factor, and prognosis of end-stage renal disease after heart transplantation in Chinese recipients - Jeng-Wei Chen; Cheng-Hsin Lin; Ron-Bin Hsu (Journal of the Formosan Medical Association, 2014)
End-stage renal disease (ESRD) is an important complication arising after heart transplantation. At least 3–10% of recipients reach ESRD within 10 years after transplant. The incidence of ESRD in Chinese recipients has not been reported. Here we sought to assess the incidence, prognosis, and risk factors for ESRD in Chinese recipients. Methods: We conducted a retrospective analysis of 248 heart recipients who survived >1 year from 1998 through 2007. ESRD was defined as the requirement of maintenance dialysis. Results: Renal dysfunction was present in 20 patients (8%) prior to transplant. With a follow-up duration of 5.8 ± 3.9 years, 30 patients developed ESRD. The cumulative incidence of ESRD after heart transplantation was 2.1% ± 0.9%, 6.5% ± 1.8%, 16.8% ± 3.3%, and 36.5% ± 9.5% at 2, 5, 10, and 15 years after transplant, respectively. Median onset of ESRD was 6.9 years after transplant. Actuarial survival after dialysis was 74.8% ± 8.3%, 66.6% ± 9.2%, and 43.6% ± 12.6% at 1, 2, and 5 years, respectively. Independent risk factors for ESRD included pretransplant serum creatinine (hazard ratio, 1.84; p = 0.001), presence of diabetes prior to transplant (hazard ratio, 2.51; p = 0.017), and old age at transplant (hazard ratio, 1.05; p = 0.008). Conclusion: There was a high incidence of ESRD in Chinese heart recipients. Patients with ESRD had poor prognosis after dialysis.